Quantifying right atrial filling and emptying: A 4D‐flow MRI study. Issue 4 (April 2017) - Callaghan, Fraser M.; Arnott, Clare; Figtree, Gemma A.; Kutty, Shelby; Celermajer, David S.; Grieve, Stuart M.
Abstract : Purpose: To quantitatively characterize the central role of vortex formation on the flow patterns and energy transfer within the right atrium (RA). Materials and Methods: 4D‐flow magnetic resonance imaging (MRI) data with multiple encoding velocities was acquired in 12 healthy subjects at 3T. Particles entering the RA were classified according to the origin of entry. Vortex membership was numerically derived by assessing the location of pathline center of curvature relative to the vortex core, defined by Q‐criteria. Flow dynamics and energetics were assessed using paired t ‐tests. Results: The majority of flow (74%) passes through the RA in a single beat, with a very small volume fraction retained longer than two beats (<1%). RA flow was dominated by a governing vortex, comprising 79% of total flow, and acting to preserve kinetic energy. Flow comprising the vortex enters the RA significantly earlier than nonvortex flow ( P < 0.01). The majority of nonvortex flow enters the RA during systole, traversing the RA via a direct path with a significantly shorter residence time and distance traveled (both P < 0.01). Conclusion: Blood flow momentum is preserved during systole within a dominant vortex, which we are able to characterize numerically using a semiautomated approach. Our analytical approach has potential for application to understanding right heart function in health and disease. Level of Evidence : 1 J. Magn. Reson. Imaging 2017;45:1–1